Successful Treatment of Cutaneous Protothecosis Due to Prototheca wickerhamii with Terbinafine - Chen Y; Gao A; Ke Y; Zhou X; Lin L; Lu S; Liu Y (Dove Medical Press, 2024)
Yue Chen,1,* Aili Gao,1,* Yanan Ke,1 Xin Zhou,1 Li Lin,2 Sha Lu,2 Yumei Liu1 1Department of Dermatology, Guangzhou Dermatology Hospital, Guangzhou, 510095, People's Republic of China; 2Department of Dermatology, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, 510120, People's Republic of China*These authors contributed equally to this workCorrespondence: Yumei Liu, Director of Department of Dermatology, Guangzhou Dermatology Hospital, Guangzhou, People's Republic of China, Tel/Fax +86- 20-83593472, Email liuyumei1109@163.comAbstract: Protothecosis, an infrequent human infection, is caused by achlorophyllic algae belonging to the genus Prototheca, particularly Prototheca wickerhamii. The skin stands as the most commonly affected organ. This report documents a case involving an 82-year-old male with Protothecosis. Histopathological analysis revealed granulomatous inflammation in the dermis, exhibiting necrotic features and hosting numerous non-budding spherical organisms. These organisms were positively stained using methenamine silver and periodic acid-Schiff stains, confirming identification as P. wickerhamii after validation through tissue culture and sequencing procedures. Initially, the patient received oral itraconazole at a dosage of 200 mg daily, accompanied by topical 1% naftifine-0.25% ketoconazole cream for a duration of 4 weeks, resulting in significant improvement. Subsequently, due to gastrointestinal discomfort presumably linked to itraconazole, terbinafine was administered. Over a span of 3 months, the patient received oral terbinafine at a dosage of 250 mg/day alongside the application of topical 1% naftifine-0.25% ketoconazole cream, leading to complete healing of the skin lesion, leaving behind a fibrotic scar.Keywords: protothecosis, Prototheca wickerhamii, terbinafine